CARACTERIZAÇÃO DE UMA UNIDADE DE PRODUÇÃO AGROPECUÁRIA DO TIPO PATRONAL GRÃOS - Basso, Nilvo; Henriques, Angélica d. O.; Maziero, Mateus; Martins, Luciane R. V.; Uhde, Leonir T.; Mumbach, Tatiele (Salão do Conhecimento, 2013)
Resumo